Peran Modal Sosial dalam Pemenuhan Kebutuhan Ekonomi Usahatani Bawang Merah Kabupaten Nganjuk - Nadzifah, Zahrotin; Mulyaningtyas, Ratna Dewi; Suparno, Suparno (Manajemen Agribisnis: Jurnal Agribisnis, 2025)
Gapoktan Amanah Sae is a farmer group located in Balonggebnag Village, Gondang District, Nganjuk Regency which has problems related to the availability of economic resources in shallot farming activities. This research aims to determine the role of social capital in providing the economic needs of shallot farming which is reviewed based on 3 components, namely resources, social structure, and actions based on the micro level and meso level. The location was chosen deliberately with the consideration that Gapoktan Amanah Sae is a Gapoktan that is active in helping farmers overcome problems in farming activities. The technique for determining informants uses purposive sampling technique. Data analysis uses Miles and Huberman analysis. The research results show that social capital can play a role in providing the economic analysis needs of shallot farming both at the micro level and meso level analysis